Confidentiality and treatment decisions of minor clients: a health professional’s dilemma & policy makers challenge - Jackson, Margot; Kovacs Burns, Katharina; Richter, Magdalena S. (My University, 2014)
Issues relating to confidentiality and consent for physical and mental health treatment with minor clients can pose challenges health care providers. Decisions need to be made regarding these issues despite the absence of clear, direct, or comprehensive policies and legislation. In order to fully understand the scope of this topic, a systemic review of several pieces of legislation and guidelines related to this topic are examined. These include the: Canadian Human Rights Act, Children’s Rights: International and National Laws and Practices, Health Information Act, Gillick Competence and Medical Emancipation, Freedom of Information and Protection of Privacy Act, Child, Youth and Family Enhancement Act, Common Law Mature Minor Doctrine, and Alberta Health Services Consent to Treatment/Practice(s) Minor/Mature Minor. In order to assist health professionals with decisions regarding confidentiality and treatment with minor clients a case study and guide for decision-making is also presented.
Keywords: confidentiality; minor clients; health legislation; health treatment; health policy